No Opioids after Septorhinoplasty: A Multimodal Analgesic Protocol. Issue 12 (December 2020) - Hall, Bradley R.; Billue, Katherine L.; Hon, Heidi; Sanders, Stacey E.; Barrientos, Stephan; Flores, Laura E.; Nicholas, Thomas; Shostrom, Valerie; Meyer, Bria; Johnson, Perry J.
Abstract : Background: From a public health perspective, nasal surgery accounts for many unused opioids. Patients undergoing septorhinoplasty require few opioids, and efforts to eliminate this need may benefit both patients and the public. Methods: A multimodal analgesic protocol consisting of 15 components encompassing all phases of care was implemented for 42 patients. Results: Median age and BMI were 34 years and 23, respectively. Most were women (79%), White (79%), primary surgeries (62%), and self-pay (52%). Comorbid conditions were present in 74% of the patients, with anxiety (33%) and depression (21%) being the most common. Septoplasties (67%) and osteotomies (45%) were common. The median operative time was 70 minutes. No patients required opioids in recovery, and median time in recovery was 63 minutes. Ten (24%) patients required an opioid prescription after discharge. In those patients, median time to requirement was 27 hours (range 3–81), and median total requirement was 20 mg morphine equivalents (range 7.5–85). Protocol compliance inversely correlated to opioid use ( P = 0.007). Compliance with local and regional anesthetic (20% versus 63%, P = 0.030) as well as ketorolac (70% versus 100%, P = 0.011) was lower in patients who required opioids. Patients who required opioids were less likely to be administered a beta blocker (0% versus 34%, P = 0.041). Pain scores were higher in opioid users on postoperative days 1–5 ( P < 0.05). No complications occurred in those requiring opioids, and satisfaction rates were equivalent between groups. Conclusion: This protocol allowed us to safely omit opioid prescriptions in 76% of patients following septorhinoplasty, without adverse effects on outcomes or patient satisfaction. Abstract : Supplemental Digital Content is available in the text.